PENERAPAN MODEL SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MEKATRONIKA- A SMK NEGERI 2 KOTA CIMAHI SEMESTER GANJIL PADA MATERI KETENTUAN UNDANG- UNDANG DASAR 1945 - Hasanah, Nani (P2M STKIP Siliwangi, 2021)
This study aims to improve student learning outcomes, especially the realm of knowledge in the provisions of the 1945 Constitution on PKN subjects with the Snowball throwing learning model in class X Mechatronics A in the odd semester of SMK 2017-2018 academic year Negeri 2 Cimahi. The research subjects were students of class X Mechatronics A in the 2017-2018 school year with 32 students consisting of 30 male students and 2 female students. This classroom action research is planned to consist of 2 cycles. Each cycle studied was adjusted to the changes to be achieved, in this study each cycle consisted of two meetings. The results of the study obtained that learning outcomes obtained KKM 75, namely the average value of 72.94 before the implementation of CAR and after CAR became 74.15 in the first cycle, and 75.18 in the second cycle. The number of students who got the KKM score also increased, before 50% CAR increased to 64.70% in the first cycle and 82.35% in the second cycle. Based on these data, it can be concluded that applying the Snowball throwing learning model can improve student learning outcomes, then there is a good response from students with the Snowball throwing learning model, where students are actually placed as learning subjects so that student activity increases.